Zeolite for preventing periparturient hypocalcemia in dairy cows: mechanisms and application strategies - Su, Xiu; Huang, Pengyu; Guo, Yuanyin; Cao, Jie (Frontiers in Veterinary Science, 2025)
Preventing milk fever and subclinical hypocalcemia remains a critical challenge in high-producing dairy cows. This review focuses on the mechanisms of zeolite and the strategies for zeolite application as a novel approach for regulating calcium metabolism during the transition period. Zeolite is reported to reduce calcium absorption through ion exchange capacity in the digestive tract, pre-activating calcium homeostasis regulatory systems and consequently allowing cows to rapidly adapt to lactation calcium demands postpartum. In addition to directly affecting calcium and phosphorus utilization, zeolite may also optimize the periparturient mineral metabolism network by modulating the phosphate-FGF23-Klotho and serotonin-PTHrP-calcium axes. Additionally, the supplementation of zeolite stabilizes ruminal pH, improves volatile fatty acid composition, enhances fiber digestibility, and promotes dry matter intake, facilitating recovery from postpartum negative energy balance. Furthermore, zeolite exerts immunomodulatory effects, alleviating excessive inflammatory responses, oxidative stress, and periparturient systemic inflammation. However, type selection, dosage control, timing, and safety must be considered for zeolite application. Natural and synthetic zeolites exhibit differential efficacies owing to their unique structural characteristics and exchange capacity. The particle size and dosage of zeolite directly influence the degree of calcium-phosphorus metabolism regulation. Long-term usage of zeolites may present safety concerns, such as aluminum accumulation. Zeolite application strategies must be optimized based on the breed, physiological stage characteristics, and synergistic effects with other preventive measures to effectively manage periparturient hypocalcemia and promote overall dairy cow health and performance.